Water Quality and Energy Consumption in Peri-Urban Agriculture: Lessons Learnt from a Real Case Study in a Municipality Close to Athens - Dionysia Santi; Christiana M. Papapostolou; Panagiotis Ktenidis (Environmental Sciences Proceedings, 2023)
The constant increase in urban population has resulted in, among others, increased food demand. Peri-urban areas are “transition zones from rural to urban land-uses located between the outer limits of urban and regional centres and the rural environment”. The local agriculture businesses and farmers are expected to be considerably mobilised in order to deal with the food security issues. Peri-urban areas could offer a viable solution for supplying the cities, as they can offer food at reasonable prices due to their proximity to the cities, which allows logistics and the related food supply chain to smoothly operate. However, cropping intensification is directly linked to increased energy and water needs, which, in some cases, comes as the result of unsustainable practices as well. Water, energy and food are closely interrelated within the nexus concept (Water–Energy–Food Nexus); water is needed for irrigating crops, energy for irrigation, etc. Fortunately, technological evolution can improve the current situation; for example, precision irrigation can help with the water issue by supplying the plant with water (and nutrients) at the right time, and renewable energy projects, i.e., solar panels, can provide a sustainable resolution to the energy supply problem. Nevertheless, modern farmers face two problems: often lack knowledge regarding these issues and the have to find water of good quality to supply their plantations. This paper aims to address these issues through a real-case study in a peri-urban, agricultural area close to Athens. The application of precision irrigation in local agricultural production is presented and the results will evidence how the farming community of the Greek municipality can benefit. Data collection concerning water quality and quantity, the types of crops cultivated, and the energy consumed per hectare are collected in order to allow the transition to more sustainable agricultural practices.